2014
DOI: 10.1107/s2052252514007283
|View full text |Cite
|
Sign up to set email alerts
|

First spin-resolved electron distributions in crystals from combined polarized neutron and X-ray diffraction experiments

Abstract: A method to map spin-resolved electron distribution from combined polarized neutron and X-ray diffraction is described and applied for the first time to a molecular magnet and it is shown that spin up density is 5% more contracted than spin down density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 16 publications
5
47
0
1
Order By: Relevance
“…[11][12][13][14][15] The multipole model is the result of necessary approximations. [23] Cross-fertilized by charge-density research, ways of directly fitting the shapes of orbitals andw avefunctions to the mea-sured diffraction pattern were also devised. [16] Furthermore, the modeling of atomicd isplacements initially led to additional problems in case of two-center electron density functions.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] The multipole model is the result of necessary approximations. [23] Cross-fertilized by charge-density research, ways of directly fitting the shapes of orbitals andw avefunctions to the mea-sured diffraction pattern were also devised. [16] Furthermore, the modeling of atomicd isplacements initially led to additional problems in case of two-center electron density functions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that spin-resolved electron density can be modelled using joint refinement against X-ray, neutron and polarized neutron diffraction data [16]. While PND gives access to the spin density in the position space, M-ICS permits to explore the spin density in the momentum space.…”
Section: Introductionmentioning
confidence: 99%
“…However, the significant breakthrough was achieved recently by combination of the results coming from different experiments using X-ray, neutron and polarized neutron diffracttion data on spin resolved electron density [19]. These experimental spin up and spin down densities compare well with density functional theory (DFT).…”
Section: Advanced and New Methods And Technologies Supporting The Devmentioning
confidence: 57%